Analisis Jabatan: Pilar Pengelolaan Sumber Daya Manusia yang Efektif - Asrin, Lulu Khulwatul Jannah; Supendi, Pepen (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study discusses job analysis which is a crucial element in human resource management. Job analysis is a process of systematically and comprehensively reviewing and collecting information about the duties, obligations, and responsibilities of employees in an organization, company, or school. Job analysis is important to understand the duties and responsibilities of employees in achieving goals. Job analysis is one of the functions of human resource management. If managers implement this, then the management of the organization that relies on hard numbers will gradually shift towards a healthy organizational climate and rely on the work responsibilities of each employee. This study includes the definition of HR job analysis, the purpose of job analysis, aspects of job analysis and the stages in making a job analysis. The results of the job analysis show that a clear understanding of duties and responsibilities can increase motivation, job satisfaction, and overall performance of educators. And most importantly, the results of the job analysis must be accurate and neatly recorded to be used as a reference in the next human resource management process. Job analysis is carried out in the human resource management planning process. The results can then be used in decision making throughout the entire human resource management process.